Coexistence Demonstration and Wavelength Dependency Analysis of S-Band CV-QKD Signal with Fully Loaded C+L-Band DWDM Signals - Tetsuo Kawakami; Hiroki Kawahara; Toshihiko Okamura; Wakako Maeda (Entropy)
We demonstrated the coexistence of an S-band CV-QKD signal with fully loaded C+L-band classical signals for the first time. The secret key rate of the S-band QKD system was 986 kbps with the C+L-band WDM signals transmitted through a 20 km G.654.E fiber link. We also revealed that the S-band CV-QKD performance limiting factor under the C+L-band WDM condition is the spontaneous Raman scattering light similar to the C-band CV-QKD performance limiting factor, confirming the validity of estimating the wavelength dependency of the secret key rate under the WDM condition from the fiber loss and the spontaneous Raman scattering light power. These results show that the CV-QKD performance under the C+L band WDM conditions becomes comparable to that under the C-band WDM conditions by wavelength design in the S-band.